Penyusunan Laporan Keuangan Menggunakan Sistem Akuntansi Instansi (Studi Kasus Pada Sekolah Menengah Kimia Analis Bogor) - Pamungkas, Bambang; Latifah, Ina Wardani (Institut Bisnis dan Informatika Kesatuan, 2013)
Law No. 17/ 2003 on State Finance requires form and content of accountability report of APBN/ APBD implementation must be arranged and presented in accordance with governmental accounting standard set by government regulation. Law No. 17/ 2003 is on State Finance and law No. 1/ 2004 on Government Treasury. Accounting Institution System is a series of manual and computerized procedures starting from data collection, recording, abstracting, financial position reporting and financial operations at the ministry/ institution. Institution Accounting System (SAI) consists of Financial Accounting System (SAK) and Management Accounting System of State-owned Assets (SIMAK-BMN). Analyzing the procedures of Institution Accounting System (SAI) is important in the process of composing financial statements for the purpose of financial accountability comprising Budget Realization Report, Balance Sheet, Note of Financial Statement and Management of State-owned Assets (BMN). Institution Accounting System (SAI) plays an important role in composing financial reports at Bogor Chemistry Analyst High School (SMAKBO) located in Jalan Binamarga I Ciheuleut, Baranangsing, Bogor Timur. It’s very influential in composing financial statements as well because each report received always use Institution Accounting System (SAI) from the beginning of expenditure process untill the data is entered into the Institution Accounting System (SAI). The purpose of this analysis is to determine how is the human resources that run the Institution Accounting System and to find out the implementation procedure of the Accounting System of Budget Users Authorization Unit and also the integration procedures of the accounting system of Budget Users Authorization Unit to Institution Accounting System (SAI). The result of the analysis of financial statement is that the procedure implemented by SMAKBO has been in accordance with the existing regulations, so that producing good and accountable financial reports. After the definition of each component of Institution Accounting System and Financial Statement has been known, It can be concluded that in carrying out procedure and financialstatement reporting it should be in accordance with the prevailing regulation and should be on time in order to yield good financial statement. And in fact, the Institution Accounting System (SAI) at Bogor Chemistry Analyst High School (SMAKBO) has been applied well, and it needs to be maintained.